Genetic Dissection of Acute Anterior Uveitis Reveals Similarities and Differences in Associations Observed With Ankylosing Spondylitis. Issue 1 (January 2015) - Robinson, Philip C.; Claushuis, Theodora A. M.; Cortes, Adrian; Martin, Tammy M.; Evans, David M.; Leo, Paul; Mukhopadhyay, Pamela; Bradbury, Linda A.; Cremin, Katie; Harris, Jessica; Maksymowych, Walter P.; Inman, Robert D.; et al.
<x xml:space="preserve">Abstract</x> Objective To use high‐density genotyping to investigate the genetic associations of acute anterior uveitis (AAU) in patients with and those without ankylosing spondylitis (AS). Methods We genotyped samples from 1, 711 patients with AAU (either primary or combined with AS), 2, 339 AS patients without AAU, and 10, 000 control subjects on an Illumina Immunochip Infinium microarray. We also used data for AS patients from previous genome‐wide association studies to investigate the AS risk locus ANTXR2 for its putative effect in AAU. ANTXR2 expression in mouse eyes was investigated by real‐time quantitative reverse transcription–polymerase chain reaction. Results A comparison between all patients with AAU and healthy control subjects showed strong association over HLA–B, corresponding to the HLA–B27 tag single‐nucleotide polymorphism rs116488202. The association of 3 non–major histocompatibility complex loci, IL23R, the intergenic region 2p15, and ERAP1, reached genome‐wide significance (P < 5 × 10−8). Five loci harboring the immune‐related genes IL10–IL19, IL18R1–IL1R1, IL6R, the chromosome 1q32 locus harboring KIF21B, as well as the eye‐related gene EYS, were also associated, reaching a suggestive level of significance (P < 5 × 10−6). Several previously confirmed AS associations demonstrated significant differences in effect size between AS patients with AAU and AS patients without AAU. ANTXR2 expression varied across eye compartments. Conclusion These findings of both novel AAU‐specific associations and associations shared with AS demonstrate overlapping but also distinct genetic susceptibility loci for AAU and AS. The associations in IL10 and IL18R1 are shared with inflammatory bowel disease, suggesting common etiologic pathways.